Barriers to healthcare for American Indians experiencing homelessness. Issue 1 (2nd January 2017) - Wille, Stephanie M.; Kemp, Katherine A.; Greenfield, Brenna L.; Walls, Melissa L.
ABSTRACT: Members of American Indian (AI) communities face many barriers to receiving both mental and physical healthcare. These barriers can have a negative effect on overall health. Barriers are compounded for AIs who are also experiencing homelessness, and AI make up a disproportionate percentage of the homeless population nationwide. In-depth semi-structured interviews were conducted with 12 service providers and 16 homeless participants in a mid-size Midwestern city to identify barriers to care for homeless participants. Key barriers identified in this study for homeless participants were: transportation, phone accessibility, discrimination, and cold and bureaucratic cultures of healthcare systems. Major barriers identified by service providers were: access to care, discrimination and mistrust, and restrictive policies. Given generally higher disease prevalence within the homeless population and health disparities within the AI community, steps should be taken to reduce barriers to healthcare.